Vitamin D Levels in Patients with and without Acne and Its Relation to Acne Severity: A Case-Control Study - Alhetheli G; Elneam AIA; Alsenaid A; Al-Dhubaibi M (Dove Medical Press, 2020)
Ghadah Alhetheli, 1 Ahmed Ibrahim Abd Elneam, 2, 3 Adel Alsenaid, 4 Mohammed Al-Dhubaibi 4 1Department of Dermatology and Cutaneous Surgery, College of Medicine, Qassim University, Buraidah, Saudi Arabia; 2Clinical Biochemistry, Department of Basic Medical Sciences, College of Medicine, Shaqra University, Dawadmi, Saudi Arabia; 3Molecular Genetics and Enzymology Department, Human Genetics Division, National Research Centre, Dokki 12622, Cairo, Egypt; 4Dermatology, Department of Medicine, College of Medicine, Shaqra University, Dawadmi, Saudi ArabiaCorrespondence: Ghadah AlhetheliDepartment of Dermatology and Cutaneous Surgery, College of Medicine, Qassim University, Buraidah, Saudi ArabiaTel +966504956030Email ghthly@qu.edu.saBackground: Vitamin D plays a significant role in the function of the immune system and it influences many dermatological diseases such as psoriasis and atopic dermatitis. The prevalence of vitamin D deficiency is growing globally, with around 30– 50% of people are known to have low levels of vitamin D. Acne vulgaris is a common inflammatory disorder of the pilosebaceous unit. Studies about the role of vitamin D in the pathogenesis of acne vulgaris have shown conflicting and nonconclusive results. Thus, the precise purpose of vitamin D has not yet been established.Objective: First, to evaluate serum levels of vitamin D through a representative sample of patients with acne vulgaris and compare it with matched healthy controls. Second, to investigate if there is a relation between serum vitamin D level and the severity of acne vulgaris.Materials and Methods: This cross-sectional study included 68 patients with acne vulgaris and 50 matched healthy controls. Serum 25-hydroxyvitamin D [25 (OH) D] levels were measured for both patients and healthy controls.Results: The study yielded lower levels of serum 25-hydroxyvitamin D in patients with acne vulgaris than its level in healthy controls. This is statistically significant with P-value = 0.003. Regarding age, gender, and sun exposure, there is no significant variation in serum 25-hydroxyvitamin D level. Also, no significant difference between the severity of acne and serum 25-hydroxyvitamin D levels.Conclusion: This study has shown clearly that vitamin D deficiency is more frequent in patients with acne with P-value = 0.003. However, no significant association between the serum level of 25-hydroxyvitamin D [25 (OH) D] and the severity of acne vulgaris. Further clinical trials on a larger scale are needed to address the importance of vitamin D in acne vulgaris. Specifically, determining whether treatment of acne with both topical vitamin D analogs and vitamin D supplementation is of significant effect.Keywords: acne vulgaris, vitamin D deficiency, 25-hydroxyvitamin D